Modeling, fabrication, and structural characterization of thin film ZnO based film bulk acoustic resonator. (2021) - Kishor Johar, Arun; Sharma, G.K.; Kumar, A.; Kumar, Hemant; Varma, T.; Periasamy, C.; Agarwal, A.; Boolchandani, D.
Abstract: This work reports the finite element modeling, fabrication and structural characterization a film bulk acoustic resonator (FBAR) devices using shadow mask technique. For the performance analysis of the FBAR device, simulations were performed on COMSOL Multiphysics platform. RF sputtering technique is used to deposit c-axis oriented zinc oxide (ZnO) thin film on Aluminum electrodes. The Aluminum electrodes were deposited using e-beam evaporation technique. The X-ray diffraction (XRD), atomic force microscopy (AFM), and scanning electron microscopy (SEM) techniques were used to examine the surface morphologies of the deposited piezoelectric film (ZnO). The quality of the deposited piezoelectric material film was measured with the help of XRD spectra and AFM is used to measure surface roughness of the deposited ZnO film and its measured value is 6.94 nm. The resonant characteristics of fabricated FBAR device are evaluated with the help of COMSOL Multiphysics simulations and the obtained values of effective electromechanical coupling constant (k 2 eff ), quality factors (Qs and Qp ) and Figure of merit are 3.0025%, 1811.3, 1711.4 and 54 (approximately), respectively.